ANALISA PERBANDINGAN BIAYA PENGGUNAAN NUTRUNNER MANUAL DAN OTOMATIS MENGGUNAKAN METODE COST & BENEFITS ANALYSIS - Ucok Mulyo Sugeng; Tahi Manurung (Fakultas teknik Universitas Muhammadiyah Jakarta, 2017)
In a situation of increasingly fierce competition in every manufacturing company, PT SZI supposedly able to apply concepts and production strategies well as improve product quality. Thus the need for the selection of the right nutrunner as an investment in the assembly process. The assembly process is the part that greatly affects the quantity and quality of production in the manufacturing industry, the faster the process of assembling the more units are produced. Likewise with the production quality, the better the nutrunner is used it will be less risk of rejection unit which will incur additional costs.Nutrunner is a tool used for tightening bolts / nuts that are powered by wind energy or electricity. The different types of energy use in nutrunner that is the term naming nutrunner automatic and manual will be compared based on several aspects that will be selected which are more efficient in the production process. In search results of the comparison, cost calculation will use the application Desoutter Rightway. After known perbandinagn some aspects costs (energy costs, productivity costs, calibraton cost, maintenance cost, and quality cost) then the analysis will be continued use Cost & Benefits Analysis to get some of the goals of this research, which is a long period of return on investment or breakeven on the project this nutrunner with Payback Period method. Besides the cost analysis is also used to find the value of benefits in order to determine whether the project is feasible and acceptable methods Return on Investment.After the data were analyzed using the method of cost and benefit analysis then obtained a long period of payback or breakeven for automatic nutrunner investment is 1.22 years and 14.63 months. As for the value of the benefits of 146%, this means that the project is acceptable because it provides the advantages of the total investment cost.